2023
DOI: 10.3390/horticulturae9010098
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Growth and Photosynthetic Rate of Cucumber Seedlings Affected by Far-Red Light Using a Semi-Open Chamber and Imaging System

Abstract: Far-red light was excluded in photosynthetic photon flux; however, recent studies have shown that it increases photosynthetic capacity. In addition, there were few studies on the whole canopy photosynthetic rate and continuous changes of morphology on cucumber seedlings affected by far-red light. This study evaluated the effect of conventional white LEDs adding far-red light on cucumber seedlings using a semi-open chamber system for the measurement of the whole canopy gas exchange rate, and the Raspberry Pi-ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 36 publications
0
2
0
Order By: Relevance
“…However, extending leaf-level measurements of photosynthetic rate to the whole-canopy level can vary depending on light interception due to leaf position and distribution [ 27 , 28 ]. [ 29 ] showed that the photosynthetic rate of whole-canopy in cucumber seedlings decreased with decreasing light interception due to the shading effect of leaf morphology. This experiment determined that there were no shading effects due to the growth of cucumber seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…However, extending leaf-level measurements of photosynthetic rate to the whole-canopy level can vary depending on light interception due to leaf position and distribution [ 27 , 28 ]. [ 29 ] showed that the photosynthetic rate of whole-canopy in cucumber seedlings decreased with decreasing light interception due to the shading effect of leaf morphology. This experiment determined that there were no shading effects due to the growth of cucumber seedlings.…”
Section: Discussionmentioning
confidence: 99%
“…Conversely, filtering far-red solar light could inhibit internode growth and leaf area enlargement in chrysanthemum and bell pepper [12]. In addition, the low R/FR treatment could increase the content of carbohydrates in many species, including tomato [13,14], turnip (Brassica rapa L. ) [15], onion [16] and cucumber [17,18]. Similarly, supplemental farred light could significantly increase the fresh weight, dry weight and stem length of lettuce [19].…”
Section: Introductionmentioning
confidence: 99%